Flipped Classrooms in applied linguistics: promoting 21st century skills for learning - Kontra H. Edit („RIK-U” Kft., 2018)
Abstract. The notion of a Flipped Classroom as a teaching approach has been around for over a decade now but it has not gained as much popularity in our region as it perhaps should or could have. As a university instructor who has experimented with this method in teaching Applied Linguistics to BA students for a few semesters now, I would like to take this opportunity to briefly introduce the flipped classroom approach and discuss both its advantages and disadvantages from a personal perspective.
https://kmf.uz.ua/wp-content/uploads/2018/11/Multicult-Diversity_Book-of-Abstracts_23-10-2018.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00006453
Keywords: Flipped Classroom; Teaching-Learning Process; Applied Linguistics